Enzalutamide after chemotherapy in advanced castration-resistant prostate cancer: the Italian Named Patient Program. (12th September 2018) - Maines, Francesca; De Giorgi, Ugo; Procopio, Giuseppe; Facchini, Gaetano; Fratino, Lucia; Sabbatini, Roberto; Gasparro, Donatello; Basso, Umberto; Mosillo, Claudia; Campadelli, Enrico; Massari, Francesco; Sava, Teodoro; et al.
Aim: To collect efficacy and safety data of enzalutamide after docetaxel, we retrospectively evaluated the Italian Named Patient Program results.Patients & methods: Two hundred and nine metastatic castration-resistant prostate cancer patients were enrolled. Median age was 73 years. Total 42.1% patients had pain, 14.4% had a performance status of two and 59.8% had a Gleason score ≥8. Total 31.1% had previously received ≥2 chemotherapies, 15.3 and 12% had been previously treated with abiraterone and cabazitaxel, respectively and 14.8% had received both.Results: Median progression-free survival and overall survival were 4.8 and 13.1 months, respectively. A prostate-specific antigen reduction ≥50% was observed in 49.1%. Total 32.7% abiraterone-pretreated patients achieved a biochemical response compared with 56% of abiraterone-naive patients.Conclusion: Enzalutamide was safe and well tolerated. Its antitumor activity in abiraterone-pretreated patients was limited.